Can we use GPS for assessing sprinting performance in rugby sevens? A concurrent validity and between-device reliability study - Lacome, M.; Peeters, A.; Mathieu, B.; Marrier, B.; Carling, C.; Piscione, J. (Biology of Sport, 2019)
The purpose of this study was to (1) provide data on maximal sprinting speed (MSS) and maximal acceleration (Amax) in elite rugby sevens players measured with GPS devices, (2) test the concurrent validity of the signal derived from a radar device and a commercially available 16 Hz GPS device, and (2) assess the between-device reliability of MSS and Amax of the same GPS. Fifteen elite rugby sevens players (90 ± 12 kg; 181 ± 8 cm; 26 ± 5 y) participated in the maximal sprinting test. A subset of five players participated in the concurrent validity and between-devices reliability study. A concurrent validity protocol compared the GPS units and a radar device (Stalker ATS II). The between-device reliability of the GPS signal during maximal sprint running was also assessed using 6 V2 GPS units (Sensoreverywhere, Digital Simulation, Paris, France) attached to a custom-made steel sled and pushed by the five athletes who performed a combined total of 15 linear 40m sprints. CV ranged from 0.5, ±0.1 % for MSS and smoothed MSS to 6.4, ±1.1 % for Amax. TEM was trivial for MSS and smoothed MSS (0.09, ±0.01) and small for Amax and smoothed Amax (0.54, ±0.09 and 0.39, ±0.06 respectively). Mean bias ranged from -1.6, ±1.0 % to -3.0, ±1.1 % for smoothed MSS and MSS respectively. TEE were small (2.0, ±0.55 to 1.6, ±0.4 %, for MSS and smoothed MSS respectively. The main results indicate that the GPS units were highly reliable for assessing MSS and provided acceptable signal to noise ratio for measuring Amax, especially when a smoothing 0.5-s moving average is used. This 16 Hz GPS device provides sport scientists and coaches with an accurate and reliable means to monitor running performance in elite rugby sevens.